THER-09. ONCOLYTIC ADENOVIRUS, DNX-2401, FOR NAIVE DIFFUSE INTRINSIC PONTINE GLIOMAS: A PHASE I CLINICAL TRIAL. (4th December 2020) - Iñigo-Marco, Ignacio; Gonzalez-Huarriz, Marisol; García-Moure, Marc; Tamayo, Ibon; Hervas, Sandra; Hernandez, Ruben; Buñales, Maria; DeAndrea, Carlos; Villalba, Maria; Jones, Chris; MacKay, Alan; Hulleman, Esther; et al.
Abstract: The objective of this trial is to determine the safety, tolerability, and toxicity of DNX-2401 in newly diagnosed DIPG patients (NCT03178032) followed by radiotherapy. Secondary endpoints are overall survival at 12 months, percentage of responses and induced immune response against tumor. Tumor biopsy was performed through the cerebellar peduncle, followed by intratumoral injection of DNX-2401 (N=12). Three patients were treated with 1x10 10 vp and given the lack of toxicity we escalated to 5x10 10 vp. The procedure was well tolerated and reduced tumor volume was demonstrated in all patients after combined treatment (virus + radiotherapy). We performed molecular studies (RNAseq and the Oncomine Childhood Research Panel from Thermo Fisher). The immune cell composition of the biopsies pre-virus injection was assessed using multiplexed quantitative immunofluorescence. T cells were hardly detectable in these tumors while macrophages were abundant. Using a multiplexed TCR-sequencing mRNA-based assay to analyze 18 available paired pre- and post-treatment samples from the trial, we detected increased clonal T cell diversity following treatment with the virus. We also measured pre and post treatment neutralizing antibodies and their relationship with survival. Finally, we performed functional studies using 2 cell lines isolated from patients included in this trial to assess the response to the virus (infectivity, viability, T-cell recognition). In summary, the virus has shown safety and efficacy in some patients. The information obtained in this clinical study would aid understanding the response of DIPG patients to viral therapies and, therefore, to better tailor this strategy to improve the survival of these patients.